A STUDY ON THE STUDENTS’ ABILITY IN PRONOUNCING ENGLISH VOWELS THAT DO NOT EXIST IN INDONESIAN BY FOURTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF FKIP UNIVERSITY OF RIAU - Yudha, Ketut Anugrah Yudha Anugrah Yudha; Ras, Fakhri Ras; ', M. Nababan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purposes of the study are to to know the ability of the students of the fourth semester of English Study Program of FKIP University of Riau in pronouncing English vowels that do not exist in Indonesian. The population of this study was the fourth semester English student department FKIP University of Riau. The instrument used by the writer in this research was a test, tape recorder it that to record the students’ pronunciation. In analyzing the data, error analysis was used the research employed students’ errors in pronouncing English vowels into separate divisions, employing the percentage descriptive analysis to count all error and interpreting the result of the data analysis. Finally, the result of the analysis shows that students are considered “Good to Excellent” in pronouncing English vowels. Keywords: Students Ability in Pronouncing and Pronouncing English Vowel Not Exist in Indonesia.